MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA INGGRIS ANAK USIA DINI MELALUI METODE BERNYANYI DI TKQ YAA BUNAYYA - Yani Pitriya; Arifah A Riyanto; Lenny Nuraeni (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2020)
Language is one aspect of development that must be improved in early childhood. English is also commonly called the second language is part of aspects of language development can be improved through the singing method. The purpose of this study is to improve children's English vocabulary through singing methods. This research is motivated by the problems that exist in TKQ Yaa Bunayya due to obstacles in mastering and memorizing English vocabulary, as well as any errors or inaccuracies pronunciation in using English. In this research, the method used is a descriptive qualitative method that is an approach that serves to give a picture of a symptom or event of a problem that occurs, where researchers directly examine the learning process of children in improving children's English vocabulary by the singing method. Data collection in this research in using observation, interview, and documentation techniques. In research data analysis techniques using qualitative analysis techniques using data reduction, data display, and concluding. The study was conducted in 5 meetings in group A with 8 children. Through singing, methods children are not easily bored in following the stages of the learning process.